ANÁLISIS DE LA DINÁMICA SECTORIAL EN LOS MUNICIPIOS COSTEROS DE SINALOA (2004-2014). - Juárez, José Luis Hernández; Cervantes, Baltazar Pérez; García, Sandra Irene Reyes; García, Marine Rosario Urías (Revista Daena: International Journal of Good Conscience)
This research aims to identify the sectors that are driving the territorial growth and the implications that these have within the coastal municipalities of Sinaloa. The analyzed information considers indicators that provides representative information of the most dynamic economic units in each municipality. The results of the study show that this region exhibits a lower growth compared with the national economy; and, about the sectorial dynamic, the tertiary sector has the highest the highest participation in the productive apparatus of the coastal municipalities, with a growth rate of 4.4%; considering the variation of the GDP in monetary terms, it indicates that a big part of this growth is due to Culiacán and Mazatlán. Therefore, in these cases, the application of a regional economic policy is recommended.